37 Years of Forest Monitoring in Switzerland: Drought Effects on Fagus sylvatica - Braun, Sabine; Hopf, Sven-Eric; Tresch, Simon; Remund, Jan; Schindler, Christian (Frontiers in Forests and Global Change, 2021)
European beech is one of the most important deciduous tree species in natural forest ecosystems in Central Europe. Its dominance is now being questioned by the emerging drought damages due to the increased incidence of severe summer droughts. In Switzerland, Fagus sylvatica have been observed in the Intercantonal Forest Observation Program since 1984. The dataset presented here includes 179176 annual observations of beech trees on 102 plots during 37 years. The plots cover gradients in drought, nitrogen deposition, ozone, age, altitude, and soil chemistry. In dry regions of Switzerland, the dry and hot summer of 2018 caused a serious branch dieback, increased mortality in Fagus sylvatica and increased yellowing of leaves. Beech trees recovered less after 2018 than after the dry summer 2003 which had been similar in drought intensity except that the drought in 2018 started earlier in spring. Our data analyses suggest the importance of drought in subsequent years for crown transparency and mortality in beech. The drought in 2018 followed previous dry years of 2015 and 2017 which pre-weakened the trees. Our long-term data indicate that the drought from up to three previous years were significant predictors for both tree mortality and for the proportion of trees with serious (>60%) crown transparency. The delay in mortality after the weakening event suggests also the importance of weakness parasites. The staining of active vessels with safranine revealed that the cavitation caused by the low tree water potentials in 2018 persisted at least partially in 2019. Thus, the ability of the branches to conduct water was reduced and the branches dried out. Furthermore, photooxidation in light-exposed leaves has increased strongly since 2011. This phenomenon was related to low concentrations of foliar phosphorus (P) and hot temperatures before leaf harvest. The observed drought effects can be categorized as (i) hydraulic failure (branch dieback), (ii) energy starvation as a consequence of closed stomata and P deficiency (photooxidation) and (iii) infestation with weakness parasites (beech bark disease and root rots).